Prognostic implication and immunological value of contactin 1 expression in pan‐cancer. Issue 2 (22nd June 2022) - Zhang, Lingyun; Zhang, Jiayu; Liu, Tianshu; Zhang, Jinguo; Cui, Yuehong
Abstract: Objective: Contactin 1 (CNTN1) is associated with developing the cancer progression and nervous system. Although increasing evidence suggests a crucial role for CNTN1 in many research areas, it is still no detailed systematic analysis of CNTN1 and the human pan‐cancer spectrum. Here, our purpose is to make a thorough investigation of CNTN1 properties across pan‐cancer types. Methods: CNTN1 mRNA expression and genomic alteration were dissected by GTEX, TCGA, and the cBioPortal database. CNTN1 expression in human organic tissues was performed via human multiple organ tissue microarrays. Furthermore, the correlations between CNTN1 and survival periods, clinical characteristics, and immune‐associated cells infiltration were performed through the TCGA database. Additionally, GSEA was carried out to delve into the biological actions of CNTN1 in pan‐cancer. Results: We discovered that CNTN1 expression was abnormal in pan‐cancer expression analysis and could predict the survival period of cancers. The primary alteration type of CNTN1 was a genomic mutation. In addition, the aberrant CNTN1 expression was found to be related to MSI, MMR, and TMB in pan‐cancer. CNTN1 was significantly related to the infiltration of immune‐associated cells in certain kinds of cancer through the ESTIMATE algorithm and TIMER database. In particular, the cancer‐associated fibroblasts indicate a negative regulation of the tumor immune microenvironment. Next, we found the most frequent signaling pathway of CNTN1 in human pan‐cancer was neuroactive ligand–receptor interaction from GSEA analysis. Conclusion: In conclusion, the investigation highlights the predictive function of CNTN1 in human pan‐cancer and affords novel insights for drawing a landscape of CNTN1 in tumorigenesis and immune regulation. Abstract : This study investigate the expression, function, and mechanism of CNTN1 in pan‐cancer. CNTN1 was differentially expressed in pan‐cancer and the aberrant expression was associated with survival prognosis. CNTN1 was associated with MMR, MSI, TMB, immune checkpoint genes, and tumor immune microenvironment. CNTN1 was related to the infiltration of immune‐associated cells and might take a negative regulation in tumor immune microenvironment.